Virtual technologies in supporting sustainable consumption : From a single-sensory stimulus to a multi-sensory experience - Laukkanen, Tommi; Xi, Nannan; Ruusunen, Nino; Hamari, Juho (Elsevier, 2021)
Virtual technologies will change the way we consume in the digital environment in the future. Such technologies can provide consumers with a multi-sensory experience in contrast to the single-sensory stimulus in the conventional online environment. As human senses play a key role in consumption choices, we argue that virtual technologies provide greater opportunities to influence consumer decisions than the present digital environment. Consequently, we suggest that virtual technologies can potentially be used to nudge consumers towards sustainable consumption. We discuss technology-assisted sensory marketing, present the cognitive and emotive aspects of virtual reality, and propose applications of virtual reality technologies to encourage sustainable consumption. Our opinion paper concludes that virtual technologies are likely to change many aspects of human life and can have significant positive effects on the environment and climate change.
Keywords: Virtual technology; Sensory marketing; Multi-sensory experience; virtual reality; sustainable consumption; fi=Tietotekniikka|en=Computer Science|